Influenza preparedness in low-resource settings: a look at oxygen delivery in 12 African countries - Belle, Janeil M; Cohen, Hillary J; Shindo, Nahoko; Lim, Matthew L; Velazquez-Berumen, Adriana; Ndihokubwayo, Jean-Bosco; Cherian, Meena N (The Journal of Infection in Developing Countries, 2010)
Background: Pandemic influenza poses a serious threat to populations in low and lower-middle income countries that face delays in access to health care and inadequately equipped facilities. Oxygen is first-line therapy for influenza-related hypoxia and a standard component of emergency respiratory resuscitation, yet remains a scarce resource in many countries. Methodology: A snapshot survey of oxygen supply and associated infrastructure was performed at 231 health centres and hospitals in twelve African countries using the World Health Organization (WHO) Tool for Situational Analysis to Assess Emergency and Essential Surgical Care. WHO Global Initiative for Emergency and Essential Surgical Care, WHO regional and country offices, and local Ministries of Health facilitated data collection from facilities surveyed. Data was stored in the WHO DataCol SQL database and computerized spreadsheet tools were used to generate descriptive statistics. Results: Ninety-nine (43.8%) of facilities surveyed reported uninterrupted access to an oxygen source and 55 (24.6%) possessed a fully functioning oxygen concentrator. Electricity was fully available at only 81 (35.1%) health facilities. Conclusions: In addition to efforts to secure vaccines and antivirals, future global influenza preparedness efforts should include investments in oxygen and associated equipment and infrastructure at first referral health facilities, to minimize morbidity and mortality from influenza in regions with limited medical resources. Increasing oxygen delivery capacity in these areas may also provide long-term, post-pandemic benefits in the management of other medical conditions of significance, including trauma, neonatal pulmonary hypofunction, and HIV-related and childhood pneumonia.